William and Mabel Meed at the Middle Lebarge Roadhouse, west shore of Lake Laberge, April 7, 1902. - University of Washington Libraries. Special Collections Division
On the occasion of Dad ['s] birthday. PH Coll 246.30 [Meed journal: "Lake Le-Barge in Winter, West ShoreThis photo was taken April 7, 1902. in front of the Middle LeBarge Roadhouse. My wife and I are shown. The sleigh containing our baggage was drawn by the white horse from White Horse to the foot of the lake. My wife was the passenger on the sleight and I went along on foot. This transportation outfit was owned by a Mr. Lewis."] To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number